2023
DOI: 10.3390/jmse11020421
|View full text |Cite
|
Sign up to set email alerts
|

A Multicontinuum-Theory-Based Approach to the Analysis of Fiber-Reinforced Polymer Composites with Degraded Stiffness and Strength Properties Due to Moisture Absorption

Abstract: Marine energy generation technologies such as wave and tidal power have great potential in meeting the need for renewable energy in the years ahead. Yet, many challenges remain associated with marine-based systems because of the corrosive environment. Conventional materials like metals are subject to rapid corrosive breakdown, crippling the lifespan of structures in such environments. Fiber-reinforced polymer composites offer an appealing alternative in their strength and corrosion resistance, but can experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Manasi Palwankar et al demonstrated a revised fixture for bolted composite joint testing that can support countersunk fasteners [ 35 ]. Studies have also looked at the environmental impact of bolted joints, corrosion-resistant alternatives, bearing performance in harsh conditions, and the effects of thermal exposure and seawater aging on bearing strength [ 36 , 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Manasi Palwankar et al demonstrated a revised fixture for bolted composite joint testing that can support countersunk fasteners [ 35 ]. Studies have also looked at the environmental impact of bolted joints, corrosion-resistant alternatives, bearing performance in harsh conditions, and the effects of thermal exposure and seawater aging on bearing strength [ 36 , 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%